Moving from a Little Tradition to a Great Tradition: Salafi Reform in Indonesia - Rosadi, Andri; Najibul Khairi Syaie, Akhmad; Saputro, Agus; Amal, Khairul (Department of Religious Studies, Faculty of Ushuluddin and Philosophy, Sunan Ampel State Islamic University Surabaya, 2024)
This article aims to examine the Salafi commitment to only refer to practices and beliefs based on evidence, which has two consequences at once, namely the potential for conflict and the process of religious literacy. Conducted in the Kampar area, this study uses a qualitative research method and is divided into two periods. The first is from September to December 2016 and the second is in 2022 after Covid-19. The second period focuses on the aspect of deepening and revalidating some important information about Salafism in Kampar through observation. The results of the research show that Salafi renewal includes aspects of beliefs and practices that are categorized as pollutants. The basis of legitimacy in the purification process is the normative argument contained in the Qur’an and authentic hadith. Embracing a religion in this context is a process of literacy, not imitation. In the end, it can be concluded that Salafi has encouraged the process of shifting from a little tradition to a large tradition in the Islamic community in Kampar.